2016
DOI: 10.1007/s00355-016-0988-6
|View full text |Cite
|
Sign up to set email alerts
|

Campaign rhetoric and the hide-and-seek game

Abstract: We present a model of political campaigning where a candidate chooses between promoting oneself (positive campaign) or attacking the rival (negative campaign). Candidates vary only by quality. Campaign choices determine the subject of public deliberation: If a candidate runs a positive campaign and his rival a negative campaign, the voters learn the quality of the "focal" candidate. Thus, negative campaigns may be used either to expose the rival candidate (informative role) or to turn attention away from onese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…• Strategic choice of campaign issues: Although traditional literature has not sufficiently examined information transmission through candidates’ decisions on what issues to emphasize, there is recently a growing literature about this issue (e.g. Bhattacharya 2016; Dragu and Fan 2016; Egorov 2015; Li and Li 2013; Polborn and Yi 2004; Schipper and Woo 2019; Zhang 2016). Polborn and Yi (2004), Li and Li (2013), Bhattacharya (2016), and Schipper and Woo (2019), like our study, analyze negative campaigning.…”
Section: Related Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…• Strategic choice of campaign issues: Although traditional literature has not sufficiently examined information transmission through candidates’ decisions on what issues to emphasize, there is recently a growing literature about this issue (e.g. Bhattacharya 2016; Dragu and Fan 2016; Egorov 2015; Li and Li 2013; Polborn and Yi 2004; Schipper and Woo 2019; Zhang 2016). Polborn and Yi (2004), Li and Li (2013), Bhattacharya (2016), and Schipper and Woo (2019), like our study, analyze negative campaigning.…”
Section: Related Literaturementioning
confidence: 99%
“…Bhattacharya 2016; Dragu and Fan 2016; Egorov 2015; Li and Li 2013; Polborn and Yi 2004; Schipper and Woo 2019; Zhang 2016). Polborn and Yi (2004), Li and Li (2013), Bhattacharya (2016), and Schipper and Woo (2019), like our study, analyze negative campaigning. 6…”
Section: Related Literaturementioning
confidence: 99%
“…As a result, social media users are provided the means to develop and send messages across social networks perpetuating online communities (Neubaum & Krämer, 2017). Bhattacharya (2016) has suggested that efforts to categorized negative campaign communications strategies into identifiable topics may be ill-considered. Depending on the intentions and motivations of political candidates, negative campaign messages may or may not solicit voter support.…”
Section: Negative Political Messages Have Positive Influencementioning
confidence: 99%